PENDIDIKAN SEKS PADA ANAK - Nurlaili Nurlaili (Marwah: Jurnal Perempuan, Agama dan Jender, 2011)
Basicly, the teaching of sex education for the child is the same as giving immunisation to him/her. The child who has got the sex education expected will has a high self control and impenetrability to the virus attack of sex unrighteous, for example pornography, deviation, or sex abused, so that the child is not easy to infects by irresponsible sex. The Sex education for the child conducted step by step as according to his/her age. Instruction of sex is conducted squarely, easy going, and does not with negative enragement to the problem of sex. Parents have to develop sportive communications, so that the child will has a emotional openness toward parents, growing up the child trust toward parents, The problems of sex are not only a problem of intimate relationship, but many problems are there, either biological, psychological, and social. In Islam, the sex education is a part of the integration of aqidah, moral, and religious education.